'I'm going to live my life for me': trans ageing, care, and older trans and gender non-conforming adults' expectations of and concerns for later life. Issue 12 (19th December 2021) - Willis, Paul; Raithby, Michele; Dobbs, Christine; Evans, Elizabeth; Bishop, Jenny-Anne
Abstract: While research on the health and wellbeing of older lesbian, gay and bisexual adults is gradually expanding, research on older trans and gender non-conforming (TGNC) adults lags behind. Current scholarship about this group raises important questions about the intersection of ageing and gender identity for enhancing care and support for older TGNC adults and the lack of preparedness of health and social professionals for meeting these needs. In this paper, we examine the accounts of 22 TGNC individuals (50–74 years) on the topic of ageing and unpack their concerns for and expectations of later life. We present qualitative findings from a study of gender identity, ageing and care, based in Wales, United Kingdom. Data were generated from two-part interviews with each participant. Four key themes are identified: (a) facilitative factors for transitioning in mid- to later life; (b) growing older as a new lease of life; (c) growing older: regrets, delays and uncertainties; and (d) ambivalent expectations of social care services. We argue that growing older as TGNC can be experienced across a multitude of standpoints, ranging from a new lease of life to a time of regret and uncertainty. We critically discuss emergent notions of trans time, precarity and uncertainty running across participants' accounts, and the implications for enhancing recognition of gender non-conformity and gender identity in social gerontology.